Assessing factors influencing people's intention to continuously use e-government systems - Arief Rahman; Panji Randilla Apriama Pangendra (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2022)
This research aims to examine key factors influencing the intention to continuously use e-government systems. An online questionnaire was distributed to 251 users of e-government systems (Jogja Smart Service), and 231 respondents met the criteria. Researchers use PLS-SEM approach to examine the responses. The study found that system quality, service quality, information quality, and trust significantly positively affected user satisfaction. In comparison, self-efficacy has a positive but not significant effect on user satisfaction. Furthermore, user satisfaction significantly positively affects the intention to continue use. The continuous use of an e-Government service is proof of the success of a service. Hence, this paper identifies substantial factors for the continued use of e-government applications. This research modified previous research models by adding the factor of Trust, which is believed to be substantial for the continuous use of e-government systems.